Ensiklopedia perkembangan anak / Carol Cooper ; penerjemah Nadia Lastiani ; editor Dyah Novieta Handayani,Telvenia A Gusnaeni,Amanda Setiorini W - Setiorini W., Amanda; Gusnaeni, Telvenia A.; Handayani,Dyah Novieta; Cooper,Carol (Erlangga, 2009)
320 hlm ilus 27 cm